Trusteeship during the Covid-19 Pandemic: Urgency and Challenges in Indonesia - Prasetio, Rizki Bagus (Indonesian Journal of Advocacy and Legal Services, 2022)
COVID-19 has had a broad impact in many sectors, including social welfare and legal certainty. During covid-19, in 2021 about 28,000 children being orphaned, and this continues to grow along with the outbreak of the Covid-19 virus in Indonesia. Constitutionally, state guarantees for children’s welfare are regulated in various laws and regulations, however, many children do not get care until they grow up, causing the child to be under trusteeship. In positive law, trusteeship has been regulated in the Civil Code, the Compilation of Islamic Law, Law 1 of 1974 and PP 29 of 2019. However, the extent to which these regulations can meet the need for trusteeship in Indonesia still needs to be studied. This paper includes the extent to which Orphan Chamber’s (Balai Harta Peninggalan or BHP) role in the trust can function correctly. This study used normative juridical research uses a statute approach through library studies. This study found and confirmed that every child is not only entitled to protection for himself. He is also entitled to protection for his property. However, some of these regulations still have various problems ranging from overlapping rules to problems in practice. Meanwhile, the existence of disharmony provisions causes the role of BHP as trustee of trustees and temporary trustees to be less than optimal. However, with the RUU BHP, the concept of trusteeship and the role of BHP institutionally and its duties and functions will be strengthened, although with various notes. Such is the case by optimizing his role as supervisory trustee in situations of natural or non-natural disasters such as the Covid-19 pandemic.